Burden of mental disorders by gender in Pakistan: analysis of Global Burden of Disease Study data for 1990–2019 - Mohsin Hassan Alvi; Tehmina Ashraf; Farah Naz; Asif Sardar; Akbar Ullah; Anita Patel; Tayyeba Kiran; Anil Gumber; Nusrat Husain (BJPsych Bulletin)
Aims and method We aimed to examine the burden of mental disorders in Pakistan over the past three decades. We used the crude data of disability-adjusted life-years (DALYs) obtained from the Global Burden of Disease Study database (1990–2019) to represent burden. Data were retrieved on 26 January 2021. Data for adults of reproductive age (aged 15–49 years) were analysed to discuss and interpret the disease burden. An analysis was conducted on total DALYs separately for the genders for ten mental disorders reported in Pakistan.